Response study of tower crane and elastic plate under dynamic complicated excitation - Fu Liu; Haopeng Chen (PLoS ONE, 2025)
Structural vibration will inevitably occur under the dynamic complicated excitations in tower crane and elastic plate system. The continuous nonlinear vibration would lead to the deterioration of the coupling state of the responses of the tower crane and the elastic plate system. This, in turn, impacts the operational stability and reduces the service life of components. Consequently, there has been scant research on response calculation of the structure in a tower crane and elastic plate system when considering such dynamic and complex excitations. To address this gap, this paper employs a spatially coupled dynamics model of the tower crane and the plate, covering the acceleration stage, the constant speed stage, and then the deceleration stage. This model incorporates typical air resistance, the Lagrange equation, and the calculation equations based on the Reissner plate theory. Additionally, emergency braking, regarded as a type of fault, is taken into account in the dynamic model. The present model is solved numerically. The feasibility of the model is validated by comparing the measured responses of the dynamic coupling model with the experimental ones. An extensive analysis is conducted on the influence of different braking times on the dynamic response. The analysis reveals that if the emergency braking time exceeds 1.5 seconds, the vibration of the plate and tower crane system is minimal. The Kurtosis Value, Factor Value, and Skewness Value exhibit high sensitivity to the dynamic responses of the plate and the swing angles. The Frequency Center demonstrates high sensitivity to the swing angle, while the Root Mean Square Frequency and Frequency Standard Deviation show high sensitivity to the plate vibration.